2023
DOI: 10.1002/advs.202300985
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Conversion‐Reaction‐Induced Alloy Interlayer for Dendrite‐Free Sulfide‐Based All‐Solid‐State Lithium‐Metal Battery

Abstract: Utilization of lithium (Li) metal anodes in all‐solid‐state batteries employing sulfide solid electrolytes is hindered by diffusion‐related dendrite growth at high rates of charge. Engineering ex‐situ Li‐intermetallic interlayers derived from a facile solution‐based conversion‐alloy reaction is attractive for bypassing the Li0 self‐diffusion restriction. However, no correlation is established between the properties of conversion‐reaction‐induced (CRI) interlayers and the deposition behavior of Li0 in all‐solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…According to the analysis details for Figure S12, it is concluded that, in all-solid-state batteries, the Pre In anode has the ability of improving interfacial compatibility and effective utilization of active Li, which is inseparable from the multifunctional interlayer formed on it. In comparison to other reports, ,,, sulfide-based solid-state cells in this work show superior performances in view of the cycling life span, capacity retention, and areal current density (Figure e), which proves the effectiveness of a generated interlayer on the improvement of metal anode/LPSCl interface stability.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…According to the analysis details for Figure S12, it is concluded that, in all-solid-state batteries, the Pre In anode has the ability of improving interfacial compatibility and effective utilization of active Li, which is inseparable from the multifunctional interlayer formed on it. In comparison to other reports, ,,, sulfide-based solid-state cells in this work show superior performances in view of the cycling life span, capacity retention, and areal current density (Figure e), which proves the effectiveness of a generated interlayer on the improvement of metal anode/LPSCl interface stability.…”
supporting
confidence: 50%
“…Further, resistance evolution of the anode interface was studied by employing in situ impedance coupled with distribution of relaxation times (DRT) spectra. With the assistance of electron-insulating LiF as a protective substance, the interlayer can effectively inhibit the destruction of LPSCl and ensure low interface resistance. The application of the Pre In anode is also evaluated in an all-solid-state cell.…”
mentioning
confidence: 99%
“…The Ag-decorated Li anode was prepared by pretreating the Li foil with AgNO 3 (0.05 M) dissolved in DME-NMP (9:1) for 30 min. The Ag-decoration could greatly improve the lithium puncture resistance. , The PEO-LLZTO (EO/Li = 15, 10 wt %) separator was prepared by the casting method, whose thickness was 80 μm . To prevent the cathode active materials dissolving into PEO that induces the noxious “polysulfide shuttling” effect, a thin layer of Li 3 PS 4 was sprayed on the top of the Li 2 S cathode with the Li 3 PS 4 precursor sol and sintered together with the cathode.…”
Section: Methodsmentioning
confidence: 99%